Effect of the diet traditional and non-traditional on the respiration and excretion in larvae of white shrimp Litopenaeus vannamei - María Alejandra Medina-Jasso; Juan Francisco Arzola-González; Pablo Piña-Valdez; Mario Nieves-Soto (Revista MVZ Cordoba, 2015)
ABSTRACT